2000
DOI: 10.1021/jo000482x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acyl Substituents on the Reaction Mechanism for Aminolyses of 4-Nitrophenyl X-Substituted Benzoates

Abstract: Second-order rate constants (k(N)) have been measured spectrophotometrically for the reaction of 4-nitrophenyl X-substituted benzoates with a series of alicyclic secondary amines in H(2)O containing 20 mol % dimethyl sulfoxide at 25.0 degrees C. The magnitude of the k(N) values increases with increasing the basicity of amines and with increasing the electron-withdrawing ability of the acyl substituent X. The Hammett plots obtained are not linear but show a break or curvature as the acyl substituent X becomes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
120
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 49 publications
17
120
2
Order By: Relevance
“…5 In contrast, the corresponding reactions of O-4-nitrophenyl thionobenzoate (2) have been suggested to proceed through a stepwise mechanism with two intermediates (e.g., T ± and T -) since the plots of k obsd vs.…”
Section: -9mentioning
confidence: 99%
See 1 more Smart Citation
“…5 In contrast, the corresponding reactions of O-4-nitrophenyl thionobenzoate (2) have been suggested to proceed through a stepwise mechanism with two intermediates (e.g., T ± and T -) since the plots of k obsd vs.…”
Section: -9mentioning
confidence: 99%
“…We have also reported that aminolysis of 4-pyridyl Xsubstituted-benzoates (5) in MeCN proceeds through a stepwise mechanism with one or two intermediates depending on the electronic nature of the substituent X, e.g., T ± and T -when X is a strong electron-withdrawing group (EWG) but T ± only when X is a weak EWG or an electron-donating group (EDG).…”
Section: Amentioning
confidence: 99%
“…We have recently reported that aminolysis of 4-nitrophenyl picolinate (6) in H 2 O containing 20 mol % DMSO proceeds through a stepwise mechanism with a cyclic intermediate as modeled by T III on the basis of a linear Brønsted-type plot with β nuc = 0.78. 12 We have shown that 6 is over 35 times more reactive than 2a.…”
Section: Bmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Besides describing the structural relationships which lead to the reactivity of carboxylic acid derivatives, the search for nucleophiles able to cleave selectively peptide and ester bonds is still a challenge in many areas of chemistry and biochemistry. [10][11][12] The development of such stable and highly reactive nucleophiles has a wide range of applications in chemical detoxification, e.g., where quantitative phosphate bond cleavage is the target.…”
Section: Introductionmentioning
confidence: 99%